Phenotypical Identification and Toxinotyping of Clostridium perfringens Isolates from Healthy and Enteric Disease-Affected Chickens - Eaftekhar Ahmed Rana; Tanvir Ahmad Nizami; Md Sayedul Islam; Himel Barua; Md Zohorul Islam (Veterinary Medicine International)
Clostridium perfringens is a ubiquitous spore-forming anaerobic pathogen that is frequently associated with enteric disease in chickens. Moreover, enterotoxin-producing C. perfringens has high zoonotic potential as well as serious public health concerns due to the emanation of food-borne intoxication. The present study was designed to isolate, identify, and toxinotype C. perfringens from both healthy and cases of necrotic or ulcerative enteritis chickens. A total of 110 samples were collected from July 2019 to February 2021. Among the samples, 38 (34.5%, 95% CI: 26.39–43.83) were positive for C. perfringens and were obtained from broiler 21 (33.3%, 95% CI: 22.91–45.67), Sonali 9 (34.6%, 95% CI: 19.31–53.88), and layer 8 (38%, 95% CI: 20.68–59.20). C. perfringens was highly prevalent (35.7%, 95% CI: 25.48–47.44) in enteritis chickens compared with healthy ones. In multiplex PCR toxinotyping, 34 (89.4%) isolates were identified as C. perfringens type A by the presence of the alpha toxin gene (cpa). Moreover, in addition to the cpa gene, 3 (14.3%, 95% CI: 4.14–35.48) broiler and 1 (11.1%, 95% CI: 0.01–45.67) Sonali isolates harbored the enterotoxin gene (cpe) and were classified as type F. However, none of the isolates carried genes encoding beta (cpb), epsilon (etx), iota (iap), or beta-2 (cpb2) toxins. Multivariable logistic regression analysis identified the following variables such as; “previously used litter materials” (OR 21.77, 95% CI 2.22–212.66, p≤0.008); intestinal lesions, “presence of ulceration” (OR 30.01, 95% CI 3.02–297.91, p≤0.004); “ballooned with gas” (OR 24.74, 95% CI 4.34–140.86, p≤0.001) and “use of probiotics” (OR 5.24, 95% CI 0.74–36.75, p≤0.095) act as risk factors for C. perfringens colonization in chicken gut. This is the first study of molecular toxinotyping of C. perfringens from healthy and enteric-diseased chickens in Bangladesh, which might have a potential food-borne zoonotic impact on human health.